Rehabilitation of Female Stroke Patients through Simple Motor Activities - Zubair, Hina; Saeed , Parveen (Nurture, 2018)
Art signify as a various approach in the creation and is influenced by the individual perception as well as their personality and temperament. Art activities have an existing and optimistic impact in psychological and physical muscle.. Objective of this study was to assess the improvement in Gross and fine motor development of female stroke patients before and after intervention through art activities This study was quantitative in nature. Mild category of Stroke patients from the rehabilitation centre were the population of this study. Two rehabilitation centres were selected on a convenient basis 30 female stroke patients was total sample size of the study. A checklist was made for the patients to recognize the before and after improvement in motor development of fine muscles. Data was entered in SPSS (Statistical Package for Social Science) .The percentages was calculated before and after intervention improvement of motor skills of female stroke patients and Statistically Paired sample T-Test were find significant value of progress through art activities. The result indicated that the P 0.000 < 0.05 there is a strong significant differences of gross and fine motor development before and after intervention through art activity. It could be concluded that art therapy is fast and quickly developing field related of Art and medical science.